Social Capital: A Literature Review In Resources Management - Yusmar Yusuf; Meyzi Heriyanto; Tri Joko Waluyo; Syafrizal; Mashur Fadli; Achmad Fajri Febrian (CV. Inara, 2021)
The subject of this study is resource management. By examining the literature that has the keyword